THE STRUCTURE OF ZINC LYSINATE-RIBOFLAVINATE COLLOID PARTICLES - Andrey Vladimirovich Blinov; Alexander Vladimirovich Serov; Alexander Alexandrovich Kravtsov; Yaroslav Vladimirovich Kaznacheev (Современная наука и инновации, 2022)
Zinc Lysinate-riboflavinate is a new advanced form of zinc essential microelement, perspective for the enrichment of whole milk products. The results of the investigation of the zinc Lysinate-riboflavinate phase composition are presented in the work. Its space group and the type of crystal lattice are established. A study of the microstructure of zinc Lysinate-riboflavinate showed that the samples consist of nee-dle-shape crystals with lengh from hundreds of nanometers to several microns. Elemental composition of substance was determined using energy-dispersive microanalysis.